Intertextuality between T. S Eliot and Al Sayyab’s poetry - Mohd Nazri, Latiff Azmi; Mohamed Ayed, Ayasrah (Canadian Center of Science and Education, 2019)
The purpose of this study is to shed light on ‘intertextuality’ as a cross cultural technique between modern Arabic and English poetry with reference to T. S Eliot and Al Sayyab. It aims to uncover the intertextual aspects of ‘allusion’, ‘symbols and myths’, ‘irony’, ‘the objective equivalent’, ‘conceptual metaphor’ and ‘impersonality’ between Eliot and Al Sayyab and the impact of Eliot’s thoughts, themes, expressions and style on Al Sayyab’s. However, the study reveals that the strategy of intertextuality takes a one-way direction, i.e., from Eliot to Al Sayyab, and Eliot’s fingerprints are quite manifest in Al Sayyab’s poetry. Moreover, although some of Eliot’s key expressions, ideas, symbols, myths and themes are borrowed by Al Sayyab, he could professionally use intertextuality and maintain his illustrious style.